Quantitative determination of Atenolol in tablets - Zhuk, Y. N.; Vasyuk, S. O.; Васюк, Світлана Олександрівна; Жук, Юлія Миколаївна (My University, 2016)
In this investigation a visible spectrophotometric method for the quantitative determination of atenolol based on the absorbance of colored product of the reaction between atenolol and bromthymol blue in acetone medium at 402 nm measurement was developed. The optimal conditions for the quantitative determination of atenolol in the content of pharmaceutical drugs were established. The stoichiometric relationship coefficients between atenolol and bromthymol blue were determined. The proposed method is valid according to the validation requirements of Ukrainian Pharmacopeia. According to the experimental data, the technique can be correctly reproduced and it is suitable for routine quality control.
Keywords: atenolol; quantitative determination; spectrophotometric method; bromthymol blue